Evidence for acupotomology in the management of cervical radiculopathy: A protocol for systematic review and meta-analysis. Issue 36 (4th September 2020) - Dai, Wenkang; Xie, Rui; Wang, Xiongwei; Zhuang, Minghui; Chang, Xiaojuan; Wei, Xu; Jin, Zhefeng; Wang, Shangquan; Feng, Minshan; Yu, Jie; Zhu, Liguo
Abstract: Background: Cervical radiculopathy (CR) describes compression or stimulation secondary to the cervical nerve root, 1 or 2 types of upper limb pain, and/or with neck. In clinical practice, both acupotomology and acupuncture are very widely and popular for the management of CR. So, we conducted a systematic review and meta-analysis to explore the efficacy, safety of acupotomology in the treatment of CR. Methods: We will search the following databases from inception to the September 2019 : MEDLINE(PubMed), Web of Science(Thomson Reuters), Cochrane Library, Embase (Ovid, Elsevier), SinoMed, Clinical Trials. gov, the China National Knowledge Infrastructure, Wanfang database, and VIP database. We will apply no language restrictions. We will not use a randomized controlled trial filter in EMBASE, as the set of intervention terms will limit the results sufficiently. The randomised controlled trials of acupotomology versus acupuncture for CR; two independent researchers will use the bias risk tool provided by the Cochrane Collaboration to evaluate the quality of the literature using RevMan 5.3 software (Copenhagen, The Nordic Cochrane Centre, The Cochrane Collaboration, 2014). Results: This systematic review and meta-analysis will provide a synthesis of existing evidence-based medical evidence for acupotomology/ acupotomy/needle knife in the treatment of CR. Conclusion: The conclusions of this systematic review and meta-analysis will provide evidence to evaluate the effectiveness of acupotomology/ acupotomy/needle knife for CR and further guide clinical decision-making. Ethics and Dissemination: This study is based on literature and therefore does not require ethical approval or patient consent. The study will be published in a peer-reviewed journal. PROSPERO registration number: CRD42020172274